Pemberdayaan Ekonomi Perempuan Berbasis Komunitas Melalui Program Satu RT Satu Kelompok Perspektif Ekonomi Islam - Eko Puji Lestari; Khusniati Rofi'ah; Luhur Prasetiyo (Institut Agama Islam Negeri Ponorogo, 2024)
The Sate Kopok Program is an initiative of the Ponorogo Regency Government to empower women at the RT level with the aim of increasing local economic productivity. Launched by Regent Sugiri Sancoko in response to the economic impact of the COVID-19 pandemic, this program provides financial support in the form of basic necessities allocated through the RT activity budget as initial capital. This study uses a field approach with qualitative methods to understand the implementation of the Sate Kopok Program, evaluate the supporting and inhibiting factors that influence its success, and assess its impact on women entrepreneurs and the community. Data were collected through interviews, FGDs, observations, and documentation, analyzed using the Miles and Huberman model, and tested using triangulation techniques. The results of the study indicate that although this program has the potential to support women's empowerment, challenges such as lack of training, low support for sustainable capital, and lack of mentoring systems hinder optimal implementation. Social and environmental factors also affect the effectiveness of the program, and lack of supervision from stakeholders causes the program to stagnate. To achieve the goal of women's economic empowerment effectively, improvements in aspects of supervision, evaluation, and further support for business groups are needed.